2022
DOI: 10.1021/acscatal.2c01534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Oxygen Evolution Reaction on NiFe2O4 and CoFe2O4 Inverse-Spinel Oxides

Abstract: Spinel ferrites, especially Nickel ferrite, NiFe 2 O 4 , and Cobalt ferrite, CoFe 2 O 4 , are efficient and promising anode catalyst materials in the field of electrochemical water splitting. Using density functional theory, we extensively investigate and quantitatively model the mechanism and energetics of the oxygen evolution reaction (OER) on the (001) facets of their inverse-spinel structure, thought as the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 73 publications
(124 reference statements)
5
43
0
Order By: Relevance
“… 38 , 68 In the case of Co-doped systems, the overpotential values for the incorporated in or deposited on species (0.36 and 0.35 V, respectively) are very close to the value of 0.38 V that was computed for the CoFe 2 O 4 (001) surface. 68 These new results prove that the same performance toward OER can be obtained by introducing a limited quantity of Co or Ni on the Fe 3 O 4 surface rather than by using Co/Fe or Ni/Fe mixed oxides and, thus, provide experimentalists a clear and practical way to cut the catalyst cost.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“… 38 , 68 In the case of Co-doped systems, the overpotential values for the incorporated in or deposited on species (0.36 and 0.35 V, respectively) are very close to the value of 0.38 V that was computed for the CoFe 2 O 4 (001) surface. 68 These new results prove that the same performance toward OER can be obtained by introducing a limited quantity of Co or Ni on the Fe 3 O 4 surface rather than by using Co/Fe or Ni/Fe mixed oxides and, thus, provide experimentalists a clear and practical way to cut the catalyst cost.…”
Section: Discussionsupporting
confidence: 73%
“…As an approximate description of the presence of the solvent, one dissociated water molecule was adsorbed on the slabs: ,, the OH fragment was adsorbed on an exposed fivefold coordinated Fe Oct III (in the case of clean DBT, Ti in @DBT, and Co in @DBT, left panels in Figure b) or on an adatom (in the case of Co ad @SCV, Ni ad @SCV, and Cu ad @SCV, right panels in Figure b), whereas the H fragment was adsorbed on an exposed surface oxygen nearby. The adsorption energy ( E Ads ) for the dissociated water molecule was calculated as follows E Ads = E total ( E surface + E H 2 O ) where E total is the total energy of the whole system (surface and adsorbed water), E surface is the energy of the isolated Fe 3 O 4 (001) surface, and E H 2 O is the energy of one isolated water molecule.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…16 Thus, decoupling the scaling relation of the intermediate species through the surface structure design on the catalyst is considered to be the best strategy for the OER. [17][18][19] However, the development of OER catalysts remains a challenge due to the high overpotentials required to drive the multi-electron and multi-proton redox reaction, which also accelerate the destruction of the highly active surface structures. It has been reported that the surface coverage of the intermediate species strongly affects the reaction kinetics at a low overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…16 Thus, decoupling the scaling relation of the intermediate species through the surface structure design on the catalyst is considered to be the best strategy for the OER. 17–19…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, energy and environmental crises are prominently noticeable and rectifiable due to the acceleration of industrialization and urbanization in and around the world. In particular, researchers are focused on developing electrocatalytic and/or photocatalytic active nanomaterials for water splitting as well as for photodegradation of organic pollutants, which are challenging but demanding research topics in this scenario. Thereby, the oxygen evolution process has drawn a lot of interest since it can produce incredibly clean hydrogen through water electrolysis, which can aid in resolving the existing issues. , The multistep four-electron transfer mechanism, however, which results in hysteretic reaction conditions, is the main bottleneck for oxygen evolution reaction (OER). To enhance the reaction kinetics, high-performance electrocatalysts such as RuO 2 and IrO 2 have been utilized.…”
Section: Introductionmentioning
confidence: 99%